Peran Kecerdasan Emosional dan Tingkat Ketergantungan Nikotin pada Niat Berhenti Merokok - Masithah, Dewi; Soedirham, Oedojo; Triyoga, Rita S. (Media Kesehatan Masyarakat Indonesia, 2019)
Smoking cessation intention is a motivating factor that influence to smoking cessation behavior. Smoking cessation intention is influenced by attitude toward smoking cessation behavior, subjective norm, and perceived behavior control. This research aims to analyze the influence of emotional intelligence and nicotine dependence level on smoking cessation intention. This research was obesevational analytic study with cross sectional design and used a quantitative approach. The population of this study were male smoker college student of state university in Madura. The sampling method used proportionate stratified random sampling with sample size 290 college student. The result of this study are emotional intelligence influenced smoking cessation intention trough attitude toward smoking cessation behavior and subjective norm. Nicotine dependence level influenced smoking cessation intention trough attitude toward smoking cessation, subjective norm, and perceived behavior control. The conclusion of this study was nicotine dependence level has more influence on smoking cessation intention than emotional intelligence.